2017
DOI: 10.1021/acschembio.7b00113
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of α-Synuclein at Serine 87 Reduces Aggregation without Affecting Membrane Binding

Abstract: The aggregation of neurodegenerative-disease associated proteins can be affected by many factors, including a variety of post-translational modifications. One such modification, O-GlcNAcylation, has been found on some of these aggregation prone proteins, including α-synuclein, the major protein that plays a causative role in synucleinopathies like Parkinson’s disease. We previously used synthetic protein chemistry to prepare α-synuclein bearing a homogeneous O-GlcNAc modification at threonine 72 and showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 31 publications
(78 reference statements)
6
100
0
Order By: Relevance
“…Unmodified α -synuclein was recombinantly expressed and purified by RP-HPLC (Figure S10). Unmodified α -synuclein exists as an unstructured random coil in solution, and consistent with our previous results, 14 O-GlcNAcylation at serine 87 did not induce any secondary structure in the protein. Not surprisingly on the basis of our structural data given above, the spectra of α -synuclein(gC87) looked identical to those of both the unmodified and O-GlcNAcylated protein controls, demonstrating that this single-atom substitution has essentially no impact on the secondary structure of α -synuclein in solution (Figure S11).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Unmodified α -synuclein was recombinantly expressed and purified by RP-HPLC (Figure S10). Unmodified α -synuclein exists as an unstructured random coil in solution, and consistent with our previous results, 14 O-GlcNAcylation at serine 87 did not induce any secondary structure in the protein. Not surprisingly on the basis of our structural data given above, the spectra of α -synuclein(gC87) looked identical to those of both the unmodified and O-GlcNAcylated protein controls, demonstrating that this single-atom substitution has essentially no impact on the secondary structure of α -synuclein in solution (Figure S11).…”
Section: Resultssupporting
confidence: 92%
“…14 Separate incubation of these proteins, as well as the O-GlcNAcylated or S-GlcNAcylated β -estrogen receptor peptides, with hOGA showed that while O-GlcNAc can be readily removed the S-GlcNAc modification was completely stable. These data are consistent with previous results obtained by using a bacterial homologue of OGA 19 and show that the hydrolysis of GlcNAc thioglycosides by hOGA observed by Vocadlo and co-workers is most likely confined to more activated leaving groups.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2730 We have previously used synthetic protein chemistry to prepare α-synuclein with O-GlcNAcylation at two of these sites, threonine 72 (T72) and serine 87 (S87). 31,32 Using a variety of biochemical experiments, we found that neither of these modifications inhibit the interaction of α-synuclein with membranes; however, both modifications inhibit protein aggregation, with O-GlcNAcylation at T72 having a stronger inhibitory effect.…”
Section: Introductionmentioning
confidence: 98%